Association of performance parameters of professional elite soccer players throughout the season - Silva, J.; Magalhaes, J.; Ascensao, A.; Seabra, A.; Rebelo, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The achievement and maintenance of an adequate level of physical fitness is a complex process, since adaptations to training and competition are specific to each individual. Thus, one of the central aspects of high performance training concerns the behaviour of the performance dynamics (Maia et al., 2001). Therefore, the purpose of this study was to analyze the association of soccer players` performance-related parameters throughout the season. Methods Twenty-two Portuguese elite professional soccer players were evaluated in four occasions throughout the season [prior pre-season (PPS), end pre-season (EPS), mid-season (MID) and end-of-season (EOS)] for counter-movement jump (CMJ), 5 and 30 m sprint (T5 and T30), agility (T-test), maximal concentric isokinetic knee extensor (KE) and flexor (KF) strength (90ºs-1), and intermittent endurance performance (YYIET2; no YYIET2 data were collected in MID due to Club match commitments). The association of soccer players` performance-related parameters throughout the season was analysed by the Pearson correlation coefficients (R). Results The SCM, T30, KE, KF and dominant leg hamstring/quadriceps ratio (H/Q-DL) R coefficients were high (p<0.05) between the different assessment moments (r ranging 0.7-0.9). In YYIET2, agility, and non-dominant leg H/Q (H/Q-NL) a lack of correlation between some season periods were observed (p>0.05). Concerning T5 performance, only a moderate correlation was found between PPS and MID. Discussion Although some parameters were sensitive to change throughout the season (SCM, H/Q-DL, YYIET2 and agility), there were differences regarding athletes` performance in the different moments. The SCM, T30, KE, KF and H/Q-DL tests had individual stability through the season, as observed by the high values of R between the different occasions. However, YYIET2, agility, H/Q-ND, and particularly T5, showed a high intraindividual variation throughout the season. This is particularly relevant as acceleration (Cometi et al., 2001) and intermittent endurance (Bangsbo et al., 2008) are essential variables to soccer high performance. Also, individual instability in H/Q ratio suggests that this parameter should be often controlled. In conclusion, data suggest that the continuous assessment of performance-related parameters throughout the season is a fundamental tool in the development of training programs suitable to the specificity of players` performance dynamics.